Understanding Factors that Affect Information Technology Outsourcing of Government Shared Services - Ahmad, Fadzilah; Ali, Rosmah; Maarop, Nurazean; Firdaus Mohd Azmi, Nurulhuda (International Journal of Engineering and Technology, 2018)
One of the Public Sector Information Communication Technology Strategic Directions for 2016 â€“ 2020 is to optimize shared services through a centralized and structured initiative. Due to some identified problems and challenges in managing the IT outsourcing arrangement, this study aims to explore the factors that could influence the success implementation of Information Technology (IT) outsourcing of government shared services (GSS) in the case of Malaysian public sector. The motivation in this study is originated from the clear problem in outsourced GSS implementation. This study was initiated by reviewing the literature on the currents issues and best practices across countries regarding the implementation of outsourcing shared services. The result is presented based on qualitative case study entailing interviews with key informants to gather information and the data analysis was performed based on the content analysis. Subsequently, nine factors that potentially influence the successful arrangement of IT outsourcing of government shared services were identified and organized into 4-domains: Strategy, Organization, Transformation and Operation.Â Â